Long-term Persistence of Anti-factor VIII Antibody-secreting Cells in Hemophilic Mice after Treatment with Human Factor VIII - Hausl, Christina; Maier, Elisabeth; Schwarz, Hans P.; Ahmad, Rafi U.; Turecek, Peter L.; Dorner, Friedrich; Reipert, Birgit M. (Thrombosis and Haemostasis, 2002)
The analysis of anti-factor VIII (FVIII) antibody-secreting cells (ASC) at different anatomic sites provides valuable information about the nature of the anti-FVIII immune response in hemophilic mice after treatment with human FVIII. An Elispot system is described that is suitable for analyzing frequencies and IgG subclasses of anti-FVIII ASC at the single-cell level. Hemophilic mice were treated with four doses of FVIII. Anti-FVIII antibodies in blood as well as anti-FVIII ASC in spleen and bone marrow were analyzed after each dose of FVIII and subsequently up to 22 weeks after termination of the FVIII treatment. Anti-FVIII ASC first appeared in the spleen where they were detectable after two intravenous doses of FVIII. Their appearance correlated with that of anti-FVIII antibodies in blood plasma. Anti- FVIII ASC in bone marrow were detectable after three doses of FVIII and were probably cells that initially formed in the spleen and subsequently migrated to the bone marrow. Whereas the frequency of anti- FVIII ASC in the spleen increased up to the fourth dose of FVIII and declined thereafter, in the bone marrow it remained constant for up to at least 22 weeks after the termination of the FVIII treatment. Titers of anti-FVIII antibodies in blood plasma increased up to the fourth dose of FVIII, then remained high constantly for 14 weeks and decreased but the antibodies were still detectable for up to at least 22 weeks after the fourth dose of FVIII. The IgG-subclass distribution of anti-FVIII ASC was similar in spleen and bone marrow and matched the subclasses of anti-FVIII antibodies in blood plasma indicating that both organs contribute to circulating antibodies in the blood.
Keywords: Hemophilia A; factor VIII; antibody-secreting cells; Elispot; animal model